Les typologies traditionnelles sont-elles fonctionnelles ? - Frédérique Jankowski (Revue d'anthropologie des connaissances)
The agronomic research claims the necessity of taking into account a multiplicity of knowledge forms. Numerous studies encourage the inclusion of local knowledge. In this context, the local taxonomies of soils are used as a scale and a unity of management allowing to include the human aspects of the environmental change, as well as a common language between scientists and farmers. Data collected in a participative research about soil vulnerability in Senegal, permit us to discuss the link existing between typologies, uses and knowledge of the agrarian soils. The study reveals the heterogeneity of local knowledge and a difference between concepts that permit to distinguishing types of soils and those used for their exploitation. While the distinction of soils is based essentially on their biophysical properties, the use strategies call for knowledge relative to the socio-technical, economic and political context. We discuss the way the context of the participative research and its methods influenced the nature of local knowledge that was collected. The heuristic value of local typology of soils appears less as a common language than an object of mutual learning between scientists and farmers.